Comparison of Blood Glucose Examination Results Using Serum and Plasma Sodium Floride (NaF) in Hyperglycemia Samples With Examination Delay Time of 30 Minutes and 1 Hour - Nur Vita Purwaningsih; Rahma Widyastuti; Haris Rizki Maulana; Ellies Tunjung Sari Maulidyanti; Lihabi Lihabi (UNIVERSITAS PGRI MADIUN, 2024)
Blood glucose level examination until now often cannot be done immediately after the sample is taken. Glycolysis in the blood can occur in vitro, thus affecting the examination results. The addition of anticoagulants such as NaF aims to inhibit the in vitro glycolysis process. Several studies have described the effects of anticoagulants in maintaining blood sugar levels in examination samples. However, the results presented still have some differences. This study aims to determine the difference in blood glucose levels using serum and plasma NaF in hyperglycemia samples with a delay of 30 minutes and 1 hour. The type of research used in this study is analytical observational with a cross-sectional approach that is a comparative study. The population in this study were all outpatients at the Muhammadiyah Hospital in Surabaya. This study was conducted at the Muhammadiyah Hospital Laboratory in Surabaya, during the study in March-April 2024. The results of this study obtained blood glucose levels using either serum or NaF plasma in hyperglycemic and non hyperglycemic samples examined with a delay of 30 minutes and 1 hour. The Greenhouse-Geisser Sig value was 0.000 (<0.05) which means there is a real (significant) difference